Depth Control for Micro-Autonomous Underwater Vehicles (μAUVs): Simulation and Experimentation. (3rd March 2014) - Watson, Simon A.; Green, Peter N.
Swarms of micro-autonomous underwater vehicles (μAUVs) are an attractive solution to the problem of nuclear storage pond monitoring. Independent movement in the horizontal and vertical planes is necessary to maximize manoeuvrability. This paper presents a comparison of different control strategies for independent depth control using both simulations and real experimental results. PID, sliding mode and a simplification of sliding mode (called 'bounded PD') are simulated using a MATLAB/SIMULINK model and are then compared to experimental results obtained when the controllers were implemented on a prototype μAUV.